Analisis Perilaku Trash-Talk Dalam Komunikasi Virtual Pada Game Online Mobile Legends - Sulton Solihin (CV. ITTC INDONESIA, 2024)
is increasingly prevalent and disruptive, negatively impacting players' personalities and involving aggressive communication. Its aim is to provide insights into the forms, effects, and importance of communication ethics in online gaming, as well as to encourage parental supervision of children playing online games. A qualitative descriptive method was employed to understand trash-talk behavior through direct observation, with data analyzed using content analysis techniques and the effective communication principles of REACH, alongside cyberbullying classification. Christine Hine's virtual ethnography approach serves as the primary foundation for this study, ensuring data validity through triangulation. Findings indicate that trash-talk behavior in Mobile Legends often involves provocation and insults that disrupt the gaming environment. The study identifies six categories of trash-talk such as animal taunts, sexuality, demeaning remarks, profanity, intellectual insults, and threats. Analysis reveals that this behavior violates principles of effective communication and falls under cyberbullying, significantly impacting players' mental well-being. In conclusion, the research highlights the importance of awareness and strategies to reduce trash-talk within the gaming community, including raising player consciousness, tightening regulations, promoting a culture of mutual respect, and supporting research and technology development to address this issue. .